Restaurant Taxation and Sustainable Economic Growth - Teresia, Apelina; Jannifer Matitaputty, Shandy (Universitas Trunojoyo Madura, 2025)
Restaurant tax is an important source of local revenue; however, persistent compliance problems indicate that tax awareness among restaurant owners does not necessarily lead to compliant behavior. This study aims to examine the behavioral and institutional foundations of restaurant tax compliance in Semarang City and to explain how awareness, intention, and institutional conditions interact in shaping compliance, with implications for sustainable regional development. Using a qualitative interpretive approach, data were collected through in-depth interviews with restaurant owners and analyzed thematically using the Theory of Planned Behavior and compliance theory. The findings reveal a clear gap between tax awareness and actual compliance, driven by weak subjective norms, limited perceived behavioral control, administrative complexity, perceived unfairness of tax rates, and low institutional trust. While sanctions are generally accepted as legitimate enforcement mechanisms, voluntary compliance is more strongly associated with transparency, tax education, administrative simplicity, and digitalized tax services. This study contributes to the local taxation literature by advancing a behavioral interpretation of local tax compliance and providing empirically grounded policy implications for strengthening sustainable regional fiscal capacity.